Possible Effect of the use of Mesenchymal Stromal Cells in the Treatment of Autism Spectrum Disorders: A Review - Tamouza, Ryad; Volt, Fernanda; Richard, Jean-Romain; Wu, Ching-Lien; Bouassida, Jihène; Boukouaci, Wahid; Lansiaux, Pauline; Cappelli, Barbara; Scigliuolo, Graziana Maria; Rafii, Hanadi; Kenzey, Chantal; Mezouad, Esma; et al. (Frontiers in Cell and Developmental Biology, 2022)
Autism spectrum disorders (ASD) represent a set of heterogeneous neurodevelopmental conditions defined by impaired social interactions and repetitive behaviors. The number of reported cases has increased over the past decades, and ASD is now a major public health burden. So far, only treatments to alleviate symptoms are available, with still unmet need for an effective disease treatment to reduce ASD core symptoms. Genetic predisposition alone can only explain a small fraction of the ASD cases. It has been reported that environmental factors interacting with specific inter-individual genetic background may induce immune dysfunctions and contribute to the incidence of ASD. Such dysfunctions can be observed at the central level, with increased microglial cells and activation in ASD brains or in the peripheral blood, as reflected by high circulating levels of pro-inflammatory cytokines, abnormal activation of T-cell subsets, presence of auto-antibodies and of dysregulated microbiota profiles. Altogether, the dysfunction of immune processes may result from immunogenetically-determined inefficient immune responses against a given challenge followed by chronic inflammation and autoimmunity. In this context, immunomodulatory therapies might offer a valid therapeutic option. Mesenchymal stromal cells (MSC) immunoregulatory and immunosuppressive properties constitute a strong rationale for their use to improve ASD clinical symptoms. In vitro studies and pre-clinical models have shown that MSC can induce synapse formation and enhance synaptic function with consequent improvement of ASD-like symptoms in mice. In addition, two preliminary human trials based on the infusion of cord blood-derived MSC showed the safety and tolerability of the procedure in children with ASD and reported promising clinical improvement of core symptoms. We review herein the immune dysfunctions associated with ASD, the rationale for using MSC to treat patients with ASD and summarize the current available studies addressing this subject.